Comprehensive treatment of heterotopic ossification in polytraumatism with traumatic brain injury case report - Muñoz-Maldonado, María Carolina (2021)
Background: Heterotopic ossification (OH) is a complication described in patients with neurological damage. Case report: Patient who suffered a multiple trauma and traumatic brain injury (TBI), with fractures and neurological deficit secondary to TBI, who presented several heterotopic ossifications (OH) during his evolution that compromised the achievement of functional objectives. The main manifestation was swelling and limitation of the articular range (RA) for the extension of the left hip and knee, which kept the lower left limb (MI) flexed, preventing standing and walking. He was diagnosed as osteoma secondary to neurological trauma and received structured medical management, which included surgical intervention: “resection of the osteoma and tenotomy in hamstrings”, obtaining improvement of the joint range, chieving standing and walking with biomechanical support. Discussion: The pathophysiology is believed to be related to the systemic release of stimulating substances from pluripotent stem cells, which differentiate as osteoblasts. Conclusion: A multidisciplinary comprehensive management provides better functional results, which contributes to the goal of the independence.